CMOS surface acoustic wave oscillators - Nordin, Anis Nurashikin; Zaghloul, Mona E.; Korman, Can; Ahmadi, Shahrokh (2005)
In this paper we describe the design and implementation of a CMOS surface acoustic wave (SAW) oscillator. The oscillator utilizes surface acoustic wave resonators implemented in both 1.6micron and 0.5micron AMI CMOS process and fabricated through MOSIS. When connected to Pierce oscillator circuits, these resonators are capable of synthesizing frequencies in the range of 400MHz to 1GHz. This paper also addresses the design issues involving codesigning micromachined resonators with CMOS circuitry to optimize the oscillator design